2019
DOI: 10.1029/2019gl084817
|View full text |Cite
|
Sign up to set email alerts
|

Dipole Structure of Mixed Layer Salinity in Response to El Niño‐La Niña Asymmetry in the Tropical Pacific

Abstract: The asymmetry of mixed layer salinity (MLS) anomalies in response to El Niño and La Niña events in the tropical Pacific is examined for the first time based on Argo observations and Estimating the Circulation and Climate of the Ocean simulation. The difference of MLS anomalies between El Niño and La Niña shows a dipole structure, with El Niño featuring strong negative salinity anomalies east of 160°E while La Niña shows remarkable positive salinity anomalies west of 160°E. A salinity budget analysis suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The data have a vertical resolution of ∼10–15 m in the upper 150 m and 25–30 m from 150–300 m. As discussed in Guan et al. (2019), the ECCO2 product has been applied in many scientific studies and has been validated with observations of oceanic circulation and water properties (e.g., Ponte & Vinogradova, 2016).…”
Section: Data Sets and Methodologymentioning
confidence: 99%
“…The data have a vertical resolution of ∼10–15 m in the upper 150 m and 25–30 m from 150–300 m. As discussed in Guan et al. (2019), the ECCO2 product has been applied in many scientific studies and has been validated with observations of oceanic circulation and water properties (e.g., Ponte & Vinogradova, 2016).…”
Section: Data Sets and Methodologymentioning
confidence: 99%
“…For example, based on 17‐year Argo observational data set, Guan, Hu, et al. (2019, hereafter G2019) found maximum salinity anomalies appear in the central equatorial Pacific during El Niño, while they are located further west in the western equatorial Pacific during La Niña. They suggested that different zonal locations of salinity anomalies may have an impact on ENSO temperature asymmetry through affecting vertical density stratification.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sustained shallow MLs favor enhanced and quick responses to wind (Maes et al., 2002; 2005). A particularly important dynamical consequence of BL is to modulate the development of El Niño (Corbett et al., 2017; Guan et al., 2019; Maes and Belamari, 2011; Maes et al., 2002; 2005; Qu et al., 2014; Zheng et al., 2014). Maes et al.…”
Section: Introductionmentioning
confidence: 99%